Tel1/ATM prevents degradation of replication forks that reverse after topoisomerase poisoning. (8th May 2018) - Menin, Luca; Ursich, Sebastian; Trovesi, Camilla; Zellweger, Ralph; Lopes, Massimo; Longhese, Maria Pia; Clerici, Michela
Abstract: In both yeast and mammals, the topoisomerase poison camptothecin (CPT) induces fork reversal, which has been proposed to stabilize replication forks, thus providing time for the repair of CPT‐induced lesions and supporting replication restart. We show that Tel1, the Saccharomyces cerevisiae orthologue of human ATM kinase, stabilizes CPT‐induced reversed forks by counteracting their nucleolytic degradation by the MRX complex. Tel1‐lacking cells are hypersensitive to CPT specifically and show less reversed forks in the presence of CPT. The lack of Mre11 nuclease activity restores wild‐type levels of reversed forks in CPT‐treated tel1 Δ cells without affecting fork reversal in wild‐type cells. Moreover, Mrc1 inactivation prevents fork reversal in wild‐type, tel1 Δ, and mre11 nuclease‐deficient cells and relieves the hypersensitivity of tel1 Δ cells to CPT. Altogether, our data indicate that Tel1 counteracts Mre11 nucleolytic activity at replication forks that undergo Mrc1‐mediated reversal in the presence of CPT. Synopsis: The topoisomerase poison camptothecin (CPT) induces fork reversal, which is thought to stabilize replication forks. Here, yeast Tel1, orthologue of human ATM, protects CPT‐induced reversed forks from nucleolytic degradation by the MRX complex. The absence of Tel1 or its kinase activity causes a specific hypersensitivity to CPT and decreases fork reversal in CPT. The decreased reversed fork levels in the absence of Tel1 are due to unscheduled nucleolytic processing that depends mainly on Mre11 nuclease activity. Tel1 function in reversed fork stabilization becomes dispensable when fork reversal is prevented by the lack of the replisome‐associated factor Mrc1, whose absence also relieves the hypersensitivity to CPT of tel1Δ cells. Abstract : The topoisomerase poison camptothecin (CPT) induces fork reversal, which is thought to stabilize replication forks. Here, yeast Tel1, orthologue of human ATM, protects CPT‐induced reversed forks from nucleolytic degradation by the MRX complex.